Migration strategies of Swan Geese Anser cygnoides from northeast Mongolia - Batbayar, Nyambayar; Takekawa, John Y; Newman, Scott H; Prosser, Diann J; Natsagdorj, Tseveenmyadag; Xiao, Xiangming (Wildfowl, 2013)
In 2006â€“2008, 25 Swan Geese Anser cygnoides were marked with solar-powered GPS satellite transmitters in northeast Mongolia to examine the timing and pathways of their migration. Most geese began their autumn migration in August, flying southeast toward a staging area at the Yalu River Estuary on the China-North Korea border. After staging for several weeks, the Swan Geese continued to their wintering grounds at wetlands along the Yangtze River Basin of eastern China in December. Spring migration commenced in late February, and the birds following either a same-route or loop migration to arrive at the breeding grounds in mid April. Swan Geese used a larger number of staging areas for a longer duration when they were north of 42Â°N latitude; they seemed to avoid staging for extended periods in the highly urbanised areas of eastern China. Further research should examine threats and disturbances to the geese in relation to human population growth and increasing urbanisation.